Comparison of distance and blended learning models on UIN Saizu Purwokerto students' learning outcomes - Yosi Intan Pandini Gunawan; Mujibur Rohman; Sania Agus Winanda; Auliya Prima Wardhani; Pinka Septiana (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2023)
The case of the Covid-19 pandemic led to a government policy to enforce online learning with distance learning and blended learning models. Lecturers are required to present learning innovations using these two models to continue to achieve maximum learning outcomes and student learning outcomes. It is through the implementation of distance learning that students can study anywhere. The blended learning model is innovative and collaborates offline/face-to-face lectures with online lectures. With the implementation of this online learning system, both distance learning and blended learning have differences in student learning outcomes. This study aims to determine the differences in student learning outcomes using distance learning and blended learning models regarding cognitive, affective, and psychomotor aspects. The research method used in this study is quantitative, with a research design using a comparative test to compare learning outcomes between two groups with different treatments. One group uses distance learning, and one group uses blended learning. The data analysis technique used to answer the hypothesis of this research is a statistic with different/comparative test, the t-test with statistical test Kolmogorov Test and Shapiro-Wilks Test to determine normality test and homogeneity test, and a nonparametric test using the Mann-Whitney test. The results showed no significant difference in cognitive, affective (activeness), and psychomotor learning achievement between students who learned to use the distance learning and blended learning models. Significant differences in learning achievement only occur in the affective aspect, particularly in student discipline in learning. Students who learn to use blended learning have better discipline than those who use distance learning.